Leitura e obtenção de conhecimento nas histórias em quadrinhos de super-heróis DC e Marvel - TELES, Jander César Reis (2021)
It investigates like the comic book Superheroes (HQ's) DC and Marvel contributes to the reading and getting the knowledge of his public reader, identifying if this type of narrative stimulates I bitt it of the reading, as well as it allows to the formation of opinions and reflections, when this reader led to getting the knowledge. It emphasizes which reasons got a beating so that the readers continued with this type of reading along the adult life. It is the question of a quanti-qualitative inquiry, under the form of study exploratória and explicative, regarding the projection of the inquiry, it was conceptualized like field work, with the instrument of the questionnaire. End that the readers look more for the enrichment of apprenticeship through the leituras, the formation of the reader is being built through the pickaninnies, new environments are being mounted and news leituras make the space of the person rich, since there are several ways in the world of the HQ's in which historically we use these tools as a fountain of information and getting the knowledge .